Impact of Covid-19 Pandemic on General Surgical Services at Karnali Academy of Health Sciences - Harihar Devkota; Suryaman Meyangbo; Sushila Khanal; Mangal Rawal (Journal of Karnali Academy of Health Sciences, 2020)
Background: Covid-19 pandemic that started from Wuhan China in 2019 December has made serious impact in the general wellbeing of people as well as the services provide by the health care institutions all over the world. This study aims to identify the impact of Covid-19 in the general surgical services provided by Karnali Academy of Health Sciences.